2013
DOI: 10.1002/grl.50876
|View full text |Cite
|
Sign up to set email alerts
|

Impact of future Arctic shipping on high‐latitude black carbon deposition

Abstract: [1] The retreat of Arctic sea ice has led to renewed calls to exploit Arctic shipping routes. The diversion of ship traffic through the Arctic will shorten shipping routes and possibly reduce global shipping emissions. However, deposition of black carbon (BC) aerosol emitted by additional Arctic ships could cause a reduction in the albedo of snow and ice, accelerating snowmelt and sea ice loss. Here we use recently compiled Arctic shipping emission inventories for 2004 and 2050 together with a global aerosol m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 33 publications
2
33
2
Order By: Relevance
“…It was our hypothesis that previous global inventories of commercial ships may be understated due to the lack of inclusion of smaller fishing vessels (<100 GT) and the use of a single emission factor that does not account for the full range of data for engine speed, engine type, fuel quality, and the ship‐to‐ship variability of a diverse fleet. The global and Arctic fuel consumption and emissions are summarized in Table for our results and previous studies [ Tyedmers et al , ; Eyring et al , ; Endresen et al , ; Dalsøren et al , ; Smith et al , ; The Arctic Council , ; Corbett et al , ; Browse et al , ; Winther et al , ; Mjelde et al , ]. We found that the global fishing fleet emits 139 Tg CO 2 yr −1 .…”
Section: Resultssupporting
confidence: 81%
“…It was our hypothesis that previous global inventories of commercial ships may be understated due to the lack of inclusion of smaller fishing vessels (<100 GT) and the use of a single emission factor that does not account for the full range of data for engine speed, engine type, fuel quality, and the ship‐to‐ship variability of a diverse fleet. The global and Arctic fuel consumption and emissions are summarized in Table for our results and previous studies [ Tyedmers et al , ; Eyring et al , ; Endresen et al , ; Dalsøren et al , ; Smith et al , ; The Arctic Council , ; Corbett et al , ; Browse et al , ; Winther et al , ; Mjelde et al , ]. We found that the global fishing fleet emits 139 Tg CO 2 yr −1 .…”
Section: Resultssupporting
confidence: 81%
“…Submicron OC particles contributed an average of 27 %, by number, from 0.13 to 1 µm with a minimum of 10 %, by number, from 0.13 to 0.2 µm and were likely from a biogenic marine source. With complete summertime sea ice loss expected by 2050 (Wang and Overland, 2015;Overland and Wang, 2013), increasing aerosol and trace gas emissions from the open Arctic Ocean are expected (Browse et al, 2013;Struthers et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Wildfire emissions represent the single largest source of emissions in the southern hemisphere. Although other sectors such as international shipping are not considered here, aerosol emissions from these sources generally have much smaller contributions to Arctic warming relative to the sectors we evaluated here, despite potentially large growth in Arctic shipping activity as sea ice retreats, and a high per‐ton impact of emissions emitted directly in the Arctic [ Browse et al , ].…”
Section: Resultsmentioning
confidence: 99%